Logical Argumentation and Persuasion in Interpersonal Communication - Alexis A. Lyle (Journal of Linguistics and Communication Studies, 2024)
Logical argumentation and persuasion are pivotal components of effective interpersonal communication. This paper examines the principles and methods of logical argumentation, the role of persuasion in communication, and how these elements intertwine to enhance understanding and influence within personal and professional interactions. By analyzing theoretical frameworks and practical applications, this paper elucidates the mechanisms through which logical argumentation and persuasive techniques can be employed to improve communication outcomes. The integration of logical, emotional, and ethical appeals is explored, highlighting their combined impact on fostering better relationships, decision-making, and influence.